The streams of knowledge: Organising the Siku Quanshu 四庫全書 - Gandolfo, S (2020)
This thesis is about the order of knowledge in the Siku Quanshu, the Complete Writings of the Four Repositories, the largest ‘encyclopaedic’ compilation of texts in pre-modern China. While contemporary scholarship has concentrated on what was included in the compilation, the question of how it was organised remains largely unexplored. Divided in five chapters, this thesis explores the understanding of knowledge and its organisation in the Qianlong era (1736–1796 CE). In the Introduction, I interrogate the methodological viability of a cross-cultural investigation and argue for a new conceptual framework to undertake such line of inquiry in the Chinese context. In Chapter 1, I show how the antecedent poetic understanding of knowledge as water determined the order of the Complete Writings. I provide an account of its impact on classification and briefly sketch its historical origins and development. By way of comparison to the western notion of knowledge as tree, I tease out the properties and cultural specificity of each system. In Chapter 2, I explore the intellectual, non-political purposes behind the collection. I provide a short overview of past bibliographic classifications and their impact on the editors’ scholarly objectives and show how the order of the Complete Writings was envisioned as an advising guide to scholarship. In Chapter 3, I identify the ascribed socio-scholarly function of texts as the fundamental principle of order and investigate the different ways in which it was expressed. I also show how the Qianlong-era conception of order differs from Aristotelian and Wittgensteinian notions of classification. In the Conclusion, I summarise the main findings of this thesis and offer some reflections on the nature of bibliographic divisions, imperial scholarship, and the Complete Writings.